Effects of caffeine supplementation on physical performance of soccer players: Systematic review and meta-analysis - Einsfeld Simões Ferreira, R.; Leite Pacheco, R.; de Oliveira Cruz Latorraca, C.; Riera, R.; Eid, R. G.; Cabrera Martimbianco, L. (Sports Health: A Multidisciplinary Approach, 2021)
Context: Caffeine is 1 of the most popular supplements consumed by athletes, and the evidence for improving soccer performance remains limited. Objective: To investigate and update the effects (benefits and harms) of caffeine to improve performance on soccer players. Data Sources: Electronic search in Medline (via PubMed), CENTRAL, Embase, SPORTDiscus, and LILACS, from inception to March 28, 2020. Study Selection: Randomized clinical trials (RCTs) assessing the effects of caffeine on the performance of soccer players. Study Design: Systematic review with meta-analysis. Level of Evidence: Level 1. Data Extraction: Data extraction was conducted independently by 2 authors using a piloted form. We assessed methodological quality (Cochrane risk-of-bias [RoB] table) and the certainty of the evidence (GRADE [Grading of Recommendations Assessment, Development and Evaluation] approach). Results: Sixteen RCTs were included. Overall methodological quality was classified as unclear to low risk of bias. When assessing aerobic endurance, meta-analyses did not demonstrate the differences between caffeine and placebo (mean difference [MD], 44.9 m; 95% confidence interval [CI], -77.7 to 167.6). Similarly, no difference was observed during time to fatigue test (MD, 169.8 seconds; 95% CI, -71.8 to 411.6). Considering anaerobic power, meta-analyses also did not find differences for vertical jump (MD, 1.01 cm; 95% CI, -0.68 to 2.69) and repeated sprint tests (MD, -0.02 seconds; 95% CI, -0.09 to 0.04), as well as reaction time agility test (MD, 0.02 seconds; 95% CI, -0.01 to 0.04) and rating of perceived exertion (MD, 0.16 points; 95% CI, -0.55 to 0.87). Regarding safety, a few minor adverse events were reported. Based on the GRADE approach, the certainty of this evidence was classified as very low to low. Conclusion: We found no significant improvement in soccer-related performance with caffeine compared with placebo or no intervention. However, caffeine appears to be safe.